Development and evaluation of matrix type transdermal patches of Simvastatin - Aftaab; Kumar, Kapil; Chauhan, Vaishali; Ikram; Rajput, Vaishali (International Journal of Indigenous Herbs and Drugs, 2023)
Transdermal patches are a cutting-edge drug delivery technology, as it avoids first-pass metabolism results in increased bioavailability and aid in the delivery of drug molecules into the systemic circulation at predetermined and controlled rate.Aim behind this invention was to formulate a stable, reproducible and non-infringing & examine matrix-type transdermal patches of Simvastatin by using solvent evaporation method and the formulation consist various polymer including HPMC, Ethyl Cellulose, Chitosan, PVPK-30 and Eudragit RS 100, plasticizers like glycerine, propylene glycol, and trietholamine are utilised, along with solvents like octanol and ethanol. The prepared patches are assessed for thickness, weight variation, folding endurance, moisture content, drug content, surface pH and in vitro diffusion studies.The results indicated that the formulation P4 showed better characteristic properties and in vitro drug diffusion.Keywords: Transdermal drug delivery system, Simvastatin, HPMC, Eudragit RS100, Ethyl Cellulose.